Peace agreements and historical end of the armed conflict - Villarraga-Sarmiento, Álvaro (Universidad Pedagógica y Tecnológica de Colombia, 2015)
Colombia has had seven decades of conflict and socio-political violence. During 1946-1957 occurred the confrontation between Liberal and Conservative parties that ended with a pact of peace, a plebiscite and the regime of the National Front. Then the confrontation between the State and left-wing guerrillas comes that lasts to the present day. The National Constituent Assemblyand theissue of the Political Constitution of 1991 allowed the consolidation of peace pacts withM19, ELN guerrillas and several regional fractions.